Flexible and Biofouling Independent Salinity Sensor. Issue 23 (23rd October 2018) - Kaidarova, Altynay; Marengo, Marco; Marinaro, Giovanni; Geraldi, Nathan; Duarte, Carlos M.; Kosel, Jürgen
Abstract: Salinity is one of the most relevant parameters in oceanography used to study properties of the oceans as well as the effects of climate change. Salinity measurements are challenging, due to the harsh environment that leads to corrosion and biofouling. In the context of animal monitors, salinity sensors should also be minimally intrusive and have a long lifetime. Here, a conductivity cell for salinity sensing is presented based on a single‐step laser irradiation process on flexible polyimide substrate. The sensors are characterized by lightweight, flexibility, low power consumption and low fabrication costs. A two‐electrode cell is used to measure the impedance, and thereby the conductivity, of the water in the MHz frequency range. It offers an accuracy of ±0.5 psu, which is not affected by sensor deformation. Deployment of the sensors in the Red Sea revealed that the materials are corrosion resistant and can withstand the harsh environment. While biofouling is strongly affecting commonly employed low frequency conductivity measurements, in the MHz frequency range, it acts like a short‐circuited capacitance. Hence, biofouling independent salinity sensing can be achieved using a two‐electrode impedance measurement at a frequency of 1 MHz. Abstract : The material properties of laser‐induced graphene are exploited for reliable salinity sensing in harsh seawater environments. The flexible and light‐weight sensors operate under various bending conditions and are fabricated by a single step process. The two‐electrode impedance measurement at high frequency is not affected by biofouling and reliably measures salinity even after several weeks of deployment in the Red Sea.